Constitutional supremacy and the rule of law: the emergence of constitutional oath doctrine - Ahmad, Muhammad Hassan; Ali Mohamed, Ashgar Ali; Ramalingam, Chithra Latha (Lexis Nexis Malaysia Sdn Bhd, 2021)
The Malaysian legal system has often been mistakenly perceived as following the parliamentary supremacy similar to the United Kingdom (UK). In fact, Malaysia practices constitutional supremacy which is fundamentally different from the UK’s legal system. The Malaysia Federal Constitution requires the judges of the superior courts to take ‘oath of office and allegiance’ before holding the office. On the basis of this, some commentators developed the ‘Constitutional Oath doctrine’ in which the judiciary is entrusted with the supreme policing authority under the Federal Constitution in upholding the rule of law. Accordingly, this article aims at evaluating the development and feasibility of this doctrine in the Malaysian legal system. It is submitted that this doctrine suited well within the Malaysian legal system which practices constitutional supremacy. This doctrine was expounded by Dr. Hamid Sultan, Court of Appeal Judge, which the learned judge has incorporated in more than 40 of his judgements. So far, this doctrine has neither been overruled nor disapproved by the apex court. Besides, it has received numerous positive reviews from both local and foreign prominent constitutional law experts.